The Problem of Legal Vacancy in the Regulation of Interim Measures and Emergency Arbitrators in the Indonesian Arbitration System as an Effort to Strengthen the Effectiveness of Decisions - Imanudin Suwardi; Subianta Mandala (Ridwan Institute, 2026)
The development of international arbitration has increasingly emphasized the need for interim protection mechanisms, such as interim measures and emergency arbitrators, to address urgent risks in modern commercial disputes. In Indonesia, Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution provides limited guidance on these mechanisms, creating legal ambiguity and potential ineffectiveness in protecting parties’ rights. This study aims to analyze the legal vacuum in regulating interim measures and emergency arbitrators within the Indonesian arbitration system and propose a normative reconstruction to enhance the effectiveness of arbitral decisions. The research employed a normative juridical approach, combining statute and conceptual methods. Data were collected from Indonesian laws, international conventions, judicial decisions, and scholarly literature, and analyzed using qualitative coding and thematic interpretation to identify gaps, ambiguities, and regulatory disharmony. The findings indicate that the current legal framework lacks explicit definitions, procedural standards, and enforcement mechanisms for interim measures, and does not recognize emergency arbitrators prior to tribunal formation. This deficiency creates temporal gaps, risks of asset dissipation, and potential conflicts with district courts, undermining the effectiveness and credibility of arbitration. The study concludes that comprehensive reform is urgently needed, including explicit legal provisions, harmonization with international standards, and structured implementation procedures, to strengthen legal certainty and the practical effectiveness of arbitration in Indonesia.